Time to go : three plays on death and dying, with commentary on end-of-life issues - Hawkins, Anne Hunsaker, 1944-; Ballard, James O.; Blaisdell, Theodore; Barta, Berry L.; Spence, Marjorie Ellen; McClelland, C. E. (University of Pennsylvania Press, 1995)
This unusual book presents three prize-winning one-act plays on the hard choices that patients, their families, and their physicians often face at the end of life. The purpose of the volume is to increase awareness and knowledge about advance directives and, beyond that, to facilitate discussion about the many complicated issues surrounding death and dying today. Each play is followed by critical commentary. The introduction provides lucid and succinct explanation of the human, ethical, and legal contexts for the rights of patients in the United States. The volume includes appendices providing values history and living will declarations, durable power of attorney statements, and resource information.